Conventional Low Intensity Pulsed-Ultrasound Therapy Increase Osteoblast, Serum Alkaline Phosphatase and Serum Calcium Levels in Fracture Healing Process - Indrayuni Lukitra Wardhani; I Ketut Gede Agus Budi Wirawan; I Putu Alit Pawana; Andriati -; Patricia Maria (Cermin Dunia Kedokteran, 2018)
Introduction: Application of ultrasound waves to improve bone healing generally use specific bone stimulator equipment not available in Indonesia. Frequency and duration of therapy from previous studies are very difficult to apply in clinical practice. This study aims to observe the therapeutic effect of conventional low-intensity pulsed-ultrasound to osteoblast, alkaline phosphatase and serum calcium levels. Method: Thirty six male white rats were divided into three groups (control, USD 5x/week, and USD 3x/week). Tibial fracture in ultrasound groups were treated 3x/week and 5x/week with ultrasound waves (1 MHz, pulsed mode, 20% of duty cycle, intensity of 0.2 W/cm2, duration 10 minutes, stationary) for 3 weeks. Callus tissue and blood from all animals were assessed quantitatively using histological and biochemical analyses. Result: Significant differences (p<0.05) in the average number of osteoblasts, level of alkaline phosphatase and serum calcium among all three groups. Conclusion: Conventional low intensity pulsed-ultrasound either 5x/week or 3x/week improve bone healing process.